2009
DOI: 10.1007/s00170-009-2094-8
|View full text |Cite
|
Sign up to set email alerts
|

Tool fabrication system for micro/nano milling—function analysis and design of a six-axis Wire EDM machine

Abstract: The dies or molds used for the fabrication of micro products usually are made of ultra-hard materials such as tungsten carbide or silicon carbide and have sophisticated three-dimensional geometries. Such kind of dies or molds can only be fabricated by milling operations instead of grinding processes with ultra-hard milling tools made of PCD or CBN. Electrical discharge machining (EDM) is a good choice for the fabrication of such ultrahard tools. In this paper, a function analysis and design of a six-axis Wire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…2, where ∑O has the X-axis pointing from O to O 1 , Y-axis pointing from O to A, and Z-axis is at the center line of the rotational axis of the ball end mill. ∑P has the X-axis pointing from P to P 1 , Y-axis pointing from O to P, and Z-axis is tangent to arc ABC at point P. Based on the generative design method as discussed in [13], line PP 1 is selected as the generating line, and arc ABC is selected as the guide line. Point P 1 represents the arbitrary point on the ball end mill geometry to be machined and overlaps P while L equals 0.…”
Section: Generative Design Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…2, where ∑O has the X-axis pointing from O to O 1 , Y-axis pointing from O to A, and Z-axis is at the center line of the rotational axis of the ball end mill. ∑P has the X-axis pointing from P to P 1 , Y-axis pointing from O to P, and Z-axis is tangent to arc ABC at point P. Based on the generative design method as discussed in [13], line PP 1 is selected as the generating line, and arc ABC is selected as the guide line. Point P 1 represents the arbitrary point on the ball end mill geometry to be machined and overlaps P while L equals 0.…”
Section: Generative Design Analysismentioning
confidence: 99%
“…A generative design method was introduced in [12] and used for a lathe design, which gave reasonable and intuitionistic answers to machine tool designs. By this method, a six-axis WEDM machine has been functionally analyzed and developed [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…This technique allows treating tool steel to its full hardness prior EDM, hence avoid the problems of geometry distortion caused by material post treatment (1) . Recently, EDM becomes a common manufacturing method to fabricate parts especially in aerospace and automobile where production quantities are relatively low (2) , mould and die industries, and small and burr-free hole drilling (3) . This process also provides an efficient way to produce delicate parts which might not be feasible by traditional machining.…”
Section: Static Edm and Orbiting Edmmentioning
confidence: 99%
“…The Wire EDM applies precise cutting action to make intricate shapes and patterns. Diamond end mills with high accuracy and edge sharpness are machined using the Wire EDM method [8,12]. A study on WEDM process optimization for PCD micro milling tool has been carried out [9].…”
Section: Introductionmentioning
confidence: 99%
“…Although it has been shown that these three methods are versatile for machining difficult-to-work materials, low machining efficiency is one of their main disadvantages. How to increase eroding speed, reduce the wear of electrode and maintain reasonable accuracy at the same time has always been the topic of EDM [11][12][13][14][15][16]. As for fabricating PCD tools, the aforementioned studies mainly focus on the methods of using the Sinker EDM and the Wire EDM [12,14,[17][18][19][20][21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%